HARMONISASI HUKUM PENGELOLAAN PENDIDIKAN TINGGI KREATIF MEDIA UNTUK PENGEMBANGAN INDUSTRI KREATIF - RR Ella Evrita H, S.E, M.M, RR Ella Evrita H, S.E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
The development of the Creative industry in Indonesia has made great progress both in terms of the achievements of people, works and creative businesses in Indonesia. This achievement means that the Creative Industry in Indonesia has the potential to continue to be developed. In addition to potential, there are also constraints with existing problems, the availability of creative, professional, and competitive resources. This can be improved by two aspects, namely Education and Capacity Building for creative workers. In addition, the development of creative industries affects interests and hobbies as well as new knowledge that will give rise to new types of education, which in this case is in accordance with Law No. 20 of 2003 concerning the National Education System Article 1 General Provisions Paragraph 2 "National Education is Education based on Pancasila and the 1945 Constitution of the Republic of Indonesia which is rooted in religious values, Indonesian national culture and is responsive to the demands of changing times”. Meanwhile, various legal products in the field of education are not entirely in line with the development of globalization. Legal products such as Education Laws and regulations already exist but when a new type of Education created by the development of globalization and technology as well as the development of creative industries appears in society according to the needs of the community, can these regulations be in accordance with that type of education? The purpose of this research is to create "Harmonization of the Legal Management of Creative Media Higher Education related to the fulfillment of the availability of creative resources (Creative People) who are professional and competitive", and "institutions that support the development of creative industries". The type or type of research chosen is normative juridical or empirical juridical which uses existing (explanatory) research and presents an explanation of the problem and tries to formulate a solution to the problem. This harmonization will be a bridge or regulation that can bridge the new type of Education with existing Education regulations and their relation to the regulations of the field itself. The point of view of this research will be focused on"Implementation of Media Creative Higher Education by Higher Education Institutions in the field of creative media. The limitations used by researchers are: 1). Legal harmonization of media creative education management with the development of creative industries. The originality obtained is: How to create a simple, easy, and friendly legal harmonization for the implementation of media creative higher education with laws related to the creative industry in Indonesia?